An analysis of increased usage of e-commerce during COVID-19 - Abdulmohsin Suliman Alkhunaizan; Ashraf Ali (Institute of Advanced Engineering and Science, 2022)
Technolgoical innovation has covered all aspects of business all over the world. With growing pace of digitalisation all over the globe, e-commerce has become one of the popular platforms for initiating business transactions. COVID-19 has showed the dependence of the society on this medium for the convenient allocation of goods and services and meeting up of consumer demands. Saudi Arabia has also witnessed a high demand in the usage of this platform to meet the daily usage necessity. In order to get insight into the topic, qualitative research has been undertaken. The study aims to investigate the increased use of e-commerce during COVID-19. The data required for the analysis has been collected from secondary sources such as web journals and research work. The finding of the qualitative analysis exhibited that the e-commerce has increased rapidly during COVID-19 time. The outcomes of the present study are helpful for the vendors to facilitate the consumers by increasing the opportunities of e-commerce.